ANALISIS PENENTUAN JUMLAH PRODUKSI STANDAR SERTA TENAGA KERJA YANG OPTIMAL PADA PRODUKSI KEMBANG GOYANG DI UMKM JATINEGARA - Pradipto, Masri; Sari, Tri Novita; Murgani, Ramli; Anggraini, Dwi (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
UMKM Kembang Goyang is one of the UMKM located in the Jatinegara area, East Jakarta. This UMKM has a flagship product in the form of kembang goyang cake. The high demand for kembang goyang cake orders, especially before Eid al-Fitr (Lebaran), with only 2 workers, makes this UMKM overwhelmed in fulfilling its production, resulting in this UMKM losing orders up to 100 packs. This study aims to calculate the processing time of each work station, standard output and the optimal number of workers needed. The method used in this study is a stopwatch time study. The stopwatch time study method is a direct measurement to obtain actual time or cycle time by considering the operator's work tempo and allowance, so that standard work time is obtained. The results show that kembang goyang cake produced from 1 kg of flour can produce 228 cakes. The standard time for kneading is 30 minutes per dough container. The standard heating time is 28 minutes per 2 liters of cooking oil. The standard time for frying until the dough is finished is 3 hours. Safety stock and defective products are set at 8 cakes, so there are 220 cakes ready to be packed at the packaging station. The standard time for packing 220 cakes into 10 packages is 30 minutes. The total time needed to make kembang goyang cakes from 1 kg of flour is 4 hours and 15 minutes. The number of workers needed at each work station is 1 person, but because this work is continuous, 1 person can work continuously from the kneading station, heating the oil, frying to packaging. If the order before Lebaran reaches 100 packages, then the number of workers needed is 10 people at each work station.